CATEGORIZING LEADERS BASED ON THEIR GAZE - Martikainen, Jari (PEOPLE: International Journal of Social Sciences, 2017)
The visual dimension of leadership has been emphasized in our contemporary, visual, era. This research discusses visual elements, and more specifically the gaze, as signs of leadership. Nine portrait paintings were shown to the participants, who were seven persons working in the field of social and health care, front-line managers and researchers. The participants were asked to reflect on the leadership qualities of the people in the paintings. The data was analyzed by membership categorization analysis in order to study what kinds of leadership categories the participants created on the basis of the visual qualities of the leaders’ gaze. Four categories of leaders were recognized in the analysis: egotistic leader, uncertain leader, indifferent leader, and communicative leader. This research raises the question of how conscious we are of the power of visual features in our interpretations of leadership, which can become concretized, for example, during recruitment.